The methods of prophylaxis of the pancreatic fistula occurrence after pancreato–duodenectomy - V. M. Kopchak; L. O. Pererva; R. V. Saliutin; V. O. Kropelnytskyi; I. V. Khomiak; O. V. Duvalko; V. P. Schkarban; Yu. O. Khilko; V. I. Trachuk; V. V. Khanenko; A. O. Danyliuk (Клінічна хірургія)
Objective. To elaborate the measures system, which permit to reduce the occurrence of pancreatic fistula and other severe complications after performance of pancreato–duodenectomy.